2013
DOI: 10.4028/www.scientific.net/amr.825.406
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Actinomycetes from Acidic Cultures of Ores and Concentrates

Abstract: Mining industry is a source of wealth but also of environmental pollution in Peru. In this study 12 colonies of actinomycetes were isolated in acidic cultures from mineral ores and concentrates from mines of the Peruvian highlands. The isolates were characterized phenotypically by microscopy and growth at different conditions as pH tolerance, temperature, and sodium chloride, heavy metals resistance; ferrous iron and thiosulfate oxidation. All isolates were identified as actinomycetes based on their cultural a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Phenothypic identification. The bacteria used in this study were isolated from minerals and ores as previously described [2]. Colony size, texture, and color of the aerial and substrate mycelium were observed on Glycerol-Yeast Extract (GYE) Agar at pH 7 and 28ºC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenothypic identification. The bacteria used in this study were isolated from minerals and ores as previously described [2]. Colony size, texture, and color of the aerial and substrate mycelium were observed on Glycerol-Yeast Extract (GYE) Agar at pH 7 and 28ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of 10, 50, 100, 200 and 400 ppm of this metal were added to standard GYE 1/10 medium. Moreover, the isolates were evaluated to determine their growth at 1.5%, 5%, 7% and 10% of sodium chloride; at pH 2.8, 4 y 7 and 8ºC, 30ºC and 45 ºC of temperatures [2]. The ability to tolerate different concentrations of mercury, growth at different conditions as pH tolerance, temperature, and sodium chloride were evaluated by abundant, regular, little or no growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of13 isolates of arsenopyrite, 9 of pyrite, 1 of polymetallic sulphide and 1 of magnetite were used. In a previous study, physiological characteristics of 6 of the 24 strains were reported (Matsubara and Hurtado, 2013).To perform the tests, Casein-Starch medium (AAC)and Glycerol-Yeast Extract medium (XGAL) (Matsubara and Hurtado, 2013) and sometimes 10% dilutions of these media were used: AAC 1/10 and XGAL 1/10. ISP4 medium Agar-starch-mineral salts was also used (Shirling and Gottlieb, 1966).…”
Section: Strains and Growth Mediummentioning
confidence: 99%
“…Also, the composition of acidic waters (Bacelar-Nicolau and Johnson, 1999) and sediments from water from mining activity (Blötheet al, 2008;Sanchez-Andrea et al, 2011) have been evaluated and the presence of sequences of Actinobacteria and sequences belonging to the order Acidimicrobiales and Actinomycetales were reported (Bacelar-Nicolauand Johnson, 1999; Blötheet al, 2008). It's been possible to isolate actinobacteria from orders different to acidimicrobiales from tailings or mining concentrates (Matsubara and Hurtado, 2013;Schippers et al, 2002), founding genres such as Catellatospora (Lee et al, 2000a), Saccharothrix (Lee et al, 2000b), Pseudonocardia (Lee et al, 2001), and Nocardiopsis metallicus (Schipperset al, 2002). Bacterial leaching or Bioleaching is a process that implies the solubilization of metals using microorganisms and it's determined by the mineralogy and other factors.…”
Section: Introductionmentioning
confidence: 99%